The Portrayal Of Chinese Fakelore In Film - Kei, Lee Kah (Universiti Malaysia Sarawak(UNIMAS), 2018)
This research is aimed to study the portrayal of Chinese fakelore in film. The manufactural or imitation of fake culture and how the adapted in fakelore must be deeply analyzed. This is due to the understanding of the fakelore inside the film are not clear among people since what they knew about fakelore film is Zhang Yimou’s film. Hence, the aim of this research is to explain and analyze the fakelore element that portrays in Chinese film. The end of the research is the applied of fakelore in storyline, costume, and props in short film as a result that captured using several methods which is analyzing the content, interview and applies method.